Few and far : the hard facts on stolen asset recovery - Gray, Larissa; Hansen, Kjetil; Recica-Kirkbride, Pranvera; Mills, Linnea (Stolen asset recovery series., 2014)
Corruption has a devastating impact on developing and transition countries, with estimates of $20 billion to $40 billion per year stolen by public officials, a figure equivalent to 20 to 40 percent of flows of official development assistance. The return of the proceeds of corruption--asset recovery--can have a significant development impact. Returns can be used directly for development purposes, such as improvements in the health and education sectors and reintegration of displaced persons, with additional benefits of improved international cooperation and enhanced capacity of law enforcement and financial management officials. Development agencies and those committed to development effectiveness have a role in the asset recovery process. They have made international commitments to fight corruption and recover the proceeds of corruption in the Third High Level Forum on Aid Effectiveness: Accra Agenda for Actions, held in Accra in 2008, and the Fourth High Level Forum on Aid Effectiveness: Partnership for Effective Development, held in Busan in 2011. Despite these efforts, there has been difficulty in translating these commitments into concrete action. This StAR-OECD publication reports on how OECD countries are performing on asset recovery. Drawing on data collected between 2006 and 2012, the report provides recommendations and good practices and suggests specific actions for development agencies. Few and Far is primarily intended to support the anti-corruption and asset recovery efforts of developed and developing jurisdictions, with a particular focus on actions for development agencies. In addition, civil society organizations engaged in governance and development issues may wish to use these findings and recommendations in their reports and advocacy efforts.